EL OPERADOR DISCURSIVO "ESO SÍ" EN ESPAÑOL Y SUS CORRESPONDENCIAS EN PORTUGUÉS - PONCE DE LEÓN, Rogelio; DUARTE, Isabel Margarida (Studia Universitatis Babeș-Bolyai Philologia, 2023)
The discourse marker eso sí in Spanish and its correspondences in Portuguese. This paper analyzes the correspondences of eso sí in Portuguese. In the first part, the predominant values of this discursive marker in Spanish are studied and its evolution from the 16th century to the present is determined. Then, the most common values as a discourse marker of isso sim are analyzed (the literal correspondence of eso sí) in current Portuguese, also establishing its evolution in the history of Portuguese until its grammaticalization as a discourse marker in the 19th century. In the second part of the paper, a contrastive analysis is carried out between these two discourse markers, establishing the convergences and divergences, according to three parameters: i) the values; ii) the position in the statement; iii) the explicitation of the negation in the sentence before the one in which the discourse marker is integrated. In the final part of the article, the correspondences of eso sí in fourteen Portuguese translations of narrative works in Spanish are presented, and their acceptability is analyzed according to the predominant value of eso sí. REZUMAT. Marcatorul discursiv eso sí în spaniolă și corespondențele sale în portugheză. Această lucrare analizează corespondențele lui eso sí în limba portugheză. În prima parte, sunt studiate valorile predominante ale acestui marcador discursiv în spaniolă și este determinată evoluția sa din secolul al XVI-lea până în prezent. Apoi, sunt analizate cele mai frecvente valori ca marcador discursiv ale lui isso sim (corespondentul literal al lui eso sí) în portugheza actuală, stabilindu-se, de asemenea, evoluția sa în istoria limbii portugheze până la gramaticalizarea sa ca marcador discursiv în secolul al XIX-lea. În partea a doua a lucrării, se realizează o analiză contrastivă a acestor doi marcadori discursivi, stabilindu-se convergențele și divergențele, în funcție de trei parametri: i) valorile; ii) poziția în enunț; iii) explicitarea negației în propoziția anterioară. În partea finală a articolului, sunt prezentate corespondențele lui eso sí în paisprezece traduceri portugheze ale unor opere narative în limba spaniolă, iar acceptabilitatea acestora este analizată în funcție de valoarea predominantă a lui eso sí. Cuvinte-cheie: marcatori discursivi, eso sí, isso sim, analiză contrastivă, traducere Article history: Received 1 August 2023; Revised 25 September 2023; Accepted 26 September 2023; Available online 20 December 2023; Available print 31 December 2023.